ANALISIS IMPLEMENTASI ANGGARAN BERBASIS KINERJA PADA PEMERINTAH DAERAH (Studi Deskriptif Pada Dinas DPKKD Kabupaten Aceh Selatan) - Nanda, Reza; Darwanis, Darwanis (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2016)
The purpose of this research is to examine the implementation of performance-based budgeting in the DPKKD department South Aceh District. Is the application appropriate according to Permendagri No. 13 2006. The collection of data and information needed in the study is conducted by field research. The data used is primary data obtained directly by interview, and secondary data through documentationThe results showed that the application of performance-based budgeting in the DPKKD department South Aceh had been going well as mandated by Permendagri No. 13 2006. However, in the implementation of its activities there are still some obstacles, such as the budget that has been planned can not be applied optimally, therefore this effects on the assessment of performance. The quality of human resources is not optimal enough, though it has already been represented and also low responsibilities of personnel departments to complete a task that becomes the main tasks and function.Keywordsbudget, performance, performance based budgeting